2020
DOI: 10.1093/cid/ciaa924
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Male Sex and Outcomes of Coronavirus Disease 2019 (COVID-19)—A Danish Nationwide, Register-based Study

Abstract: Abstract Background and objectives Male sex has been associated with severe Coronavirus disease 2019 (Covid-19) infection. We examined the association between male sex and severe Covid-19 infection and if an increased risk remains after adjustment for age and comorbidities. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
85
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 28 publications
12
85
4
6
Order By: Relevance
“…There was no difference in the proportion of men and women, which was inconsistent with the results of a study that have been conducted by Guan et al (2020) who observed that men were more likely to be infected than women. The same result has been demonstrated by a Danish team (Kragholm et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…There was no difference in the proportion of men and women, which was inconsistent with the results of a study that have been conducted by Guan et al (2020) who observed that men were more likely to be infected than women. The same result has been demonstrated by a Danish team (Kragholm et al, 2020).…”
Section: Discussionsupporting
confidence: 83%
“…This is also evident by the proportion of asymptomatic cases (15.2%) in our cohort that is less than that described in many similar studies [22]. Thus, the overall infection mortality rate among individuals with Covid-19 infections is likely to be considerably lower as it has been estimated by the CDC and WHO to be around 0.5-1% [23,24]. On the other hand, the reported case fatality rates may have been underestimated considering that several fatal Covid-19 infections remain undiagnosed [25].…”
Section: Discussioncontrasting
confidence: 45%
“…A debate is ongoing on the interplay between SARS-CoV-2 infection and the impairment of the immune system typical of autoimmune diseases [32]. A recent registry-based analysis of 4842 COVID-19 Danish hospitalized patients with COVID-19 reported an excess risk (on average more than 50%) of adverse outcomes, including mortality and ICU admission in men versus women regardless of age and comorbidities, questioning the central role of advanced age and multi-morbidities in explaining the male predominance [33]. Notably, the age of the Danish cohort was on average lower and women were younger than men across all age ranges as the opposite occurred in our cohort of hospitalized deceased individuals.…”
Section: Discussionmentioning
confidence: 99%